Na grade: protótipo de alta fidelidade para plataforma de revenda de ingressos - DIAS, Jade Nascimento; PERES, Luisa Ribeiro; ALEXADRINO, Miriam Mendes (209, 2025)
O projeto Na Grade tem como objetivo o desenvolvimento de um protótipo de aplicativo voltado para a revenda de ingressos musicais, com foco em User Experience (UX) e User Interface (UI). A proposta busca repensar a experiência do público jovem em plataformas de revenda, oferecendo uma solução que seja intuitiva, acessível e visualmente alinhada com o universo da música e dos eventos ao vivo. Para isso, o estudo envolveu pesquisa com usuários reais, análise de referências, definição de identidade visual, criação de um Design System e desenvolvimento de telas funcionais que priorizam usabilidade, clareza e identificação com o público-alvo. Na Grade foi desenvolvido pelos alunos do curso de Design de Mídias Digitais da Fatec Barueri, na disciplina de Trabalho de Graduação II, sob a orientação do Prof. Dr. Marcelo Eloy Fernandes.

The objective of this work was to study the possible implementation of a zero fare system for public road transport in the city of Barueri, located in the state of São Paulo, as well as its impacts on local sustainable urban mobility. To this end, it was necessary to understand how local urban mobility works; understand what public transport is; understand the composition of public transport fares; study the demand in the Barueri region; understand the free public transport and its influence on the movement of citizens, the reduction in the use of private vehicles, the reduction of carbon dioxide emissions and the promotion of social inclusion. Economic, social and environmental aspects were discussed, in addition to citing some examples of such implementation in some Brazilian cities. The following methods were adopted to develop this work: case study, applied research, explanatory research, bibliographical research, survey research and qualitative research. It was observed that, although there are financial and logistical challenges, the zero fare system can be an important instrument to promote more sustainable and equitable urban mobility in the city of Barueri
On the grid: high-fidelity prototype for ticket resale platform
Keywords: Protótipo; Comunicação digital; Informação e Comunicação